A Study on Assessing the Relationship between Green Marketing and Brand Loyalty in Manufacturing Sector of Greece: A Moderating Role of Green Supply Chain Practices - Anwaruddin Tanwari PhD (LifeSciFi, 2020)
This study aimed to measure the relationship between green marketing and brand loyalty in manufacturing sector of Greece. Along with that, the researcher has measured the moderating effect of green supply chain practices between green marketing and customer loyalty. The paper has adopted a quantitative research design along with incorporation of primary data collected through survey questionnaire. The sample size considered was 350 respondents with a response rate of 91.1%. The data is analysed through Structural Equation Modelling (SEM) which includes Confirmatory Factor Analysis (CFA) and path assessment techniques. The results of this study have revealed that green branding and green supply chain practices have a significant association and positive with brand loyalty. Green supply chain practices significantly and positively moderate the relationship between green branding and brand loyalty whereas, the relationship between green advertising and brand loyalty is significantly but negatively moderated by green supply chain practices. The study is only limited to the Greek manufacturing companies and has only taken into consideration the quantitative design. The concerns over environmental harm are increasing and thus, firms are giving consideration to green SCM practices. Therefore, it is important to examine whether these green SCM practices and green marketing contribute towards brand and customer loyalty or not.